2007
DOI: 10.1021/ja068602r
|View full text |Cite
|
Sign up to set email alerts
|

Model for Antibiotic Optimization via Neoglycosylation:  Synthesis of Liponeoglycopeptides Active against VRE

Abstract: The neoglycosylation of a methoxyamine-appended vancomycin aglycon with all possible N'-decanoylglucopyranose and N'-biphenoylglucopyranose regioisomers led to the production of a focused set of liponeoglycopeptide variants in good yields and with excellent stereoselectivity. High-throughput antibacterial assays employing a unique set of vancomycin-resistant Enterococci faecalis and Enterococci faecium clinical isolates revealed that the nature and regiochemistry of glycosyl lipidation modulated vancomycin-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 24 publications
2
47
3
Order By: Relevance
“…FT-MALDI Lipo-neo-glycopeptides Neoglycosylation of methoxyamineappended vancomycin aglycon (Griffith, et al, 2007) O-Mannosylated peptides (fluorescently labelled) TOF, ESI As components for synthetic vaccines: comparison of two synthetic strategies (Brimble, et al, 2008) MUC1 Glycopeptides L-, R-TOF (DHB)…”
Section: Helical Glycopeptidesmentioning
confidence: 99%
“…FT-MALDI Lipo-neo-glycopeptides Neoglycosylation of methoxyamineappended vancomycin aglycon (Griffith, et al, 2007) O-Mannosylated peptides (fluorescently labelled) TOF, ESI As components for synthetic vaccines: comparison of two synthetic strategies (Brimble, et al, 2008) MUC1 Glycopeptides L-, R-TOF (DHB)…”
Section: Helical Glycopeptidesmentioning
confidence: 99%
“…48 Since vancomycin is readily available from commercial sources, we synthesized 3 on multi-gram scale (15 g) via a sequential formation of alloc-carbamates, ally-ester and allyl-ethers. 15,48,49 From our initial screening, we found that symmetric anhydrides worked well for the acyl-transfer reactions; while acyl chlorides showed unselective reactivity and N -hydroxysuccinimide active esters were not reactive under the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…86 The latest variant of the tetracycline class, tigecycline, incorporates a glycyl linker at C9 of 9-aminodoxycycline reminiscent to that used in neoglycosylation strategies toward betulinic acid, 15 colchicine, 20 and vancomycin. 21 A four-step scheme was used to nitrate and attach methoxyglycine to the doxycycline scaffold followed by neoglycosylation with 31 different sugars ( 14 , see Table 3). 26 To extend the study of neoglycosylation, aminosugars were also used, which marks the first instance of these sugars being systematically employed in neoglycosylation.…”
Section: Section 4 – Natural Product and Small Molecule Drug Discovermentioning
confidence: 99%
“…21 Based on the structure of the related teicoplanin antibiotic, the natural disaccharide of vancomycin was replaced with 2-,3-,4-, or 6- N -decanoyl or biphenoyl D-glucose using a methoxyaminoethyl tether at the phenol of the vancomycin aglycon ( 15 ). Resulting testing against 15 VRE strains of varying resistance found that alteration of the sugar moiety improved activity against VRE strains with the 3- and 4-acylated sugars identified as the best sugars in this context.…”
Section: Section 4 – Natural Product and Small Molecule Drug Discovermentioning
confidence: 99%